Porphyrin‐Based Conducting Polymer Hydrogel for Supercapacitor Application. Issue 6 (6th April 2020) - Das, Debasree; Kurungot, Sreekumar
Abstract : Herein, the electrochemical properties and energy storage capability of a flexible, all‐solid‐state supercapacitor based on the supramolecular assembly of polypyrrole (PPy) and the anion of 5, 10, 15, 20‐tetrakis(4‐sulfonatophenyl)‐21H, 23H‐porphine manganese(III) chloride (MnTSPP) are reported. The electrode material consists of a conductive polymer hydrogel formed through the gelation initiated by cross‐linking of the dopant MnTSPP anion in the PPy chains. The morphology of the cross‐linked polymer hydrogel is that of a particle‐decorated nanofiber, which can perform as a flexible supercapacitor electrode material with a specific capacitance of 300 Fg −1 and capacitance retention of 78% up to 10 000 cycles. The anion of MnTSPP plays a pivotal role in enhancing the charge storage capability by facilitating the electron transfer between the polymer interchains. In addition, the steric hindrance due to the large size of the dopant counter ions of MnTSPP reduces the counterion drain effect and structural pulverization of PPy, thereby improving the capacitive retention. Abstract : A novel 5, 10, 15, 20‐tetrakis(4‐sulfonatophenyl)‐21H, 23H‐porphine manganese (III) chloride (MnTSPP) doped polypyrrole hydrogel is prepared to construct an all solid state supercapacitor (ASSP) device. For the demonstration of the ASSP, a 2.4 V red light‐emitting diode is powered by connecting three such solid supercapacitors in series to provide the required voltage.